If a point P(x, y) is equidistant from the points A (6,-1) and B(2,3)find the relation between X and Y.
Answers
Answered by
12
Distance between two points
![= \sqrt{(x2 -x1) {}^{2} + (y 2 - y1) {}^{2} } = \sqrt{(x2 -x1) {}^{2} + (y 2 - y1) {}^{2} }](https://tex.z-dn.net/?f=+%3D++%5Csqrt%7B%28x2+-x1%29+%7B%7D%5E%7B2%7D++%2B+%28y+2+-+y1%29+%7B%7D%5E%7B2%7D++%7D+)
AP=
![\sqrt{(x - 6) {}^{2} + (y - ( - 1) {}^{2} } \sqrt{(x - 6) {}^{2} + (y - ( - 1) {}^{2} }](https://tex.z-dn.net/?f=+%5Csqrt%7B%28x+-+6%29+%7B%7D%5E%7B2%7D++%2B+%28y+-+%28+-+1%29+%7B%7D%5E%7B2%7D+%7D+)
![= \sqrt{(x {}^{2} + 36 - 12x) + (y + 1) {}^{2} } = \sqrt{(x {}^{2} + 36 - 12x) + (y + 1) {}^{2} }](https://tex.z-dn.net/?f=+%3D++%5Csqrt%7B%28x++%7B%7D%5E%7B2%7D++%2B+36+-+12x%29+%2B+%28y+%2B+1%29+%7B%7D%5E%7B2%7D+%7D+)
![= \sqrt{ {x}^{2} + 36 - 12x + {y}^{2} + 1 + 2y} = \sqrt{ {x}^{2} + 36 - 12x + {y}^{2} + 1 + 2y}](https://tex.z-dn.net/?f=+%3D++%5Csqrt%7B+%7Bx%7D%5E%7B2%7D++%2B+36+-+12x+%2B++%7By%7D%5E%7B2%7D+%2B+1++%2B+2y%7D+)
![= \sqrt{ {x}^{2} + {y}^{2} - 12x + 2y + 37 } = \sqrt{ {x}^{2} + {y}^{2} - 12x + 2y + 37 }](https://tex.z-dn.net/?f=+%3D++%5Csqrt%7B+%7Bx%7D%5E%7B2%7D++%2B++%7By%7D%5E%7B2%7D++-+12x+%2B+2y+%2B+37+%7D+)
AP^2
![= ( \sqrt{ {x}^{2} + y {}^{2} - 12x + 2y + 37 } ){}^{2} = ( \sqrt{ {x}^{2} + y {}^{2} - 12x + 2y + 37 } ){}^{2}](https://tex.z-dn.net/?f=+%3D+%28+%5Csqrt%7B+%7Bx%7D%5E%7B2%7D+%2B+y+%7B%7D%5E%7B2%7D++-+12x+%2B+2y+%2B+37+%7D++%29%7B%7D%5E%7B2%7D+)
![= {x}^{2} + {y}^{2} - 12x + 2y + 37 = {x}^{2} + {y}^{2} - 12x + 2y + 37](https://tex.z-dn.net/?f=+%3D++%7Bx%7D%5E%7B2%7D++%2B++%7By%7D%5E%7B2%7D++-+12x+%2B+2y+%2B+37)
BP
![= \sqrt{(x - 2) {}^{2} + (y - 3) {}^{2} } = \sqrt{(x - 2) {}^{2} + (y - 3) {}^{2} }](https://tex.z-dn.net/?f=+%3D++%5Csqrt%7B%28x+-+2%29+%7B%7D%5E%7B2%7D+%2B++%28y+-+3%29+%7B%7D%5E%7B2%7D+%7D+)
![= \sqrt{ {x}^{2} + 4 - 4x + {y}^{2} + 9 - 6y} = \sqrt{ {x}^{2} + 4 - 4x + {y}^{2} + 9 - 6y}](https://tex.z-dn.net/?f=+%3D++%5Csqrt%7B+%7Bx%7D%5E%7B2%7D++%2B+4+-+4x+%2B++%7By%7D%5E%7B2%7D++%2B+9+-+6y%7D+)
![= \sqrt{ {x}^{2} + {y}^{2} - 4x - 6y + 13 } = \sqrt{ {x}^{2} + {y}^{2} - 4x - 6y + 13 }](https://tex.z-dn.net/?f=+%3D++%5Csqrt%7B+%7Bx%7D%5E%7B2%7D++%2B++%7By%7D%5E%7B2%7D+-+4x+-+6y+%2B+13+%7D+)
BP^2
![= (\sqrt{x {}^{2} + y {}^{2} - 4x - 6y + 13} ) {}^{2} = (\sqrt{x {}^{2} + y {}^{2} - 4x - 6y + 13} ) {}^{2}](https://tex.z-dn.net/?f=+%3D++%28%5Csqrt%7Bx+%7B%7D%5E%7B2%7D++%2B+y+%7B%7D%5E%7B2%7D++-+4x+-+6y+%2B+13%7D+%29+%7B%7D%5E%7B2%7D+)
![= {x}^{2} + {y}^{2} - 4x - 6y + 13 = {x}^{2} + {y}^{2} - 4x - 6y + 13](https://tex.z-dn.net/?f=+%3D++%7Bx%7D%5E%7B2%7D++%2B++%7By%7D%5E%7B2%7D++-+4x+-+6y+%2B+13)
AP^2 = BP^2
x^2 + y^2 -12 x +2 y +37 = x^2 + y^2 -4x -6y +13
-12x+2y +37 = -4x -6y +13
2y +6y = -4x +12 x +13-37
8y = 8x - 24
dividing the equation by 8 .
y=x - 3
3 = x-y
This is the required relationship.
AP=
AP^2
BP
BP^2
AP^2 = BP^2
x^2 + y^2 -12 x +2 y +37 = x^2 + y^2 -4x -6y +13
-12x+2y +37 = -4x -6y +13
2y +6y = -4x +12 x +13-37
8y = 8x - 24
dividing the equation by 8 .
y=x - 3
3 = x-y
This is the required relationship.
Similar questions